Changes in the ecosystem service values of typical river basins in arid regions of Northwest China. Issue 6 (26th July 2013) - Huang, X.; Ma, J. X.; Shen, Yanjun; Chen, Yaning; Liu, Changming
ABSTRACT This study compared the 1994 and 2005 ecosystem service values of the Tarim, Manas, Shiyang and Heihe River Basins, which are four typical examples of river basins in the arid region of Northwest China. The ecosystem areas and service values were obtained from their consumer price indices, and constant prices were calculated on the basis of data from the Land Use Classification Map of 1994, TM images, CBERS images of 2005 and research results from 'the equivalent factor table of China's ecosystem service value'. The results indicated that between 1994 and 2005 in these four river basins, the land areas supporting the environment and society (i.e. forest, grassland and wetland ecosystem) generally declined, whereas areas of farmland significantly increased. The changes in these areas in smaller basins were larger and occurred more rapidly. The ecosystem service value of the Tarim River Basin was the largest and local residents would rather pay more money for its ecosystem services, which means that the ecosystem service value there had a higher scarcity. The increase in the ecosystem service value of the Heihe River Basin was the largest. The ecosystem service value of the Heihe River Basin had more important and direct influences on the population's productivity and lives than did the Tarim River Basin. In addition, the farmland area in the Tarim River Basin increased more than the other river basins; however, the people's willingness to pay for farmland ecosystem services in this basin was the lowest. Willingness to pay was not linked to resource richness, and the concepts of economic development, water utilization and soil protection need to be strengthened. Copyright © 2013 John Wiley & Sons, Ltd.